The Andaman day gecko paradox: an ancient endemic without pronounced phylogeographic structure - Ashwini V. Mohan (Nature Portfolio, 2020)
Abstract The Andaman day gecko (Phelsuma andamanensis) is endemic to the Andaman Archipelago, located ~ 6000 km away from Madagascar where the genus Phelsuma likely evolved. We complemented existing phylogenetic data with additional markers to show that this species consistently branches off early in the evolution of the genus Phelsuma, and this early origin led us to hypothesize that island populations within the Andaman Archipelago could have further diversified. We sampled the Andaman day gecko from all major islands in the Andamans, developed new microsatellite markers and amplified mitochondrial markers to study population diversification. We detected high allelic diversity in microsatellites, but surprisingly poor geographical structuring. This study demonstrates that the Andaman day gecko has a panmictic population (K = 1), but with weak signals for two clusters that we name ‘North’ (North Andaman, Middle Andaman, Interview, Baratang, Neil, and Long Islands) and ‘South’ (Havelock, South Andaman, Little Andaman Islands). The mitochondrial COI gene uncovered wide haplotype sharing across islands with the presence of several private haplotypes (except for the Little Andaman Island, which only had an exclusive private haplotype) signalling ongoing admixture. This species differs from two other Andaman endemic geckos for which we provide comparative mitochondrial data, where haplotypes show a distinct phylogeographic structure. Testing population history scenarios for the Andaman day gecko using Approximate Bayesian Computation (ABC) supports two possible scenarios but fails to tease apart whether admixture or divergence produced the two weak clusters. Both scenarios agree that admixture and/or divergence prior to the onset of the last glacial maximum shaped the genetic diversity and structure detected in this study. ABC supports population expansion, possibly explained by anthropogenic food subsidies via plantations of cash crops, potentially coupled with human mediated dispersal resulting in the observed panmictic population. The Andaman day gecko may thus be a rare example of an island endemic reptile benefiting from habitat modification and increased movement in its native range.